A Robust Numerical Method for a Singularly Perturbed Semilinear Problem with Integral Boundary Conditions (Contemporary Mathematics, 2024)
In the present study, we provide an efficient numerical approach for solving singularly perturbed nonlinear ordinary differential equations with two integral boundary conditions. We specifically propose a numerical approach for the solution of a nonlinear singular perturbed problem with integral boundary conditions. To solve the nonlinear singularly perturbed issue, we also apply finite difference methods. It explores how a specific derivative and a problemsolving approach behave. Finally, a numerical technique that employs a finite difference scheme is built using a nonuniform mesh.
Keywords: singularly perturbed; numerical solution; boundary layer; uniform convergence